Fingerprint synthesis toward construct enhanced Authentication System using low resolution Webcam - Islam, Md. Rajibul; Sayeed, Md. Shohel; Samraj, Andrews (2008)
Synthesis of several biometrics to improve the authentication performance has received significant attention over recent years due to a rising demand for reliable user identity authentication system. In this paper we present an approach to synthesis same biometrics because during capturing fingerprint it is not confirm that all minutiae of the whole fingerprint will be obtained in every ingestion. It is very essential to obtain whole minutiae from a fingerprint when we are using minutiae matching technique for fingerprint authentication. This paper introduces an Enhanced Authentication System using fingerprint synthesis by Projection Incorporated Subspace based on PCA (Principal Component Analysis). We have used a low resolution webcam to capture fingerprint images. So, an improved fingerprint image enhancement approach is presented. In the proposed approach, the traditional minutiae detection technique has been improved using fingerprint synthesis by Projection Incorporated Subspace based on PCA. The paper presents an analysis of why fingerprint synthesis approach is well suited for fingerprint enrolment, especially for the performance improvement of the minutiae extraction algorithm. Experimental results show that our approach is insensate to low resolution as well as with effectual performance and very effective for minutiae detection to improve authentication system.